THE ROLE OF SCOUT EDUCATION IN DEVELOPMENT SCOUT MEMBER - Indah Aulia Rambe; Nafisah Nadia; Najwa Nazhira (CV. Asry Persada Quality, 2024)
The type of research used in this research is qualitative research. The data collection techniques used in this research are as follows: (1) Observation (Observation, documentation and traiangulation. Research results: The Scout Movement is an organization that pays great attention to education and self-development for all its members. In order to provide guidelines for Scout Movement quartirs and units to improve the abilities and skills of adult members so they can carry out their roles in the Scout Movement environment, the National Kwartir (Kwarnas) issued a Decree regarding the Scout Movement's Education and Training System (Sisdiklat). Kwarnas Decree No. 48 of 2018 is a refinement of the previous kwarnas decision as a form of system that synergistically integrates various components, input components, training process, results and impact of an adult member scouting training